CUSTOMER SATISFACTION TOWARDS E- BANKING SERVICES – A STUDY OF HDFC AND ICICI BANK - KOLANCHINATHAN, G.; ELANGO, Dr.S. (The journal of contemporary issues in business and government, 2021)
Banking during Roman times was not as we understand banking in modern times. During the Participate, the majority of banking activities were conducted by private individuals, and not by large banking corporations that exist today. Internet banking-Internet banking is changing the banking industry and is having the major effects on banking relationships. Banking is now no longer confined to the branches were one has to approach the branch in person, to withdraw cash or deposit a cheque or request a statement of accounts. In true Internet banking, any inquiry or transaction is processed online without any reference to the branch (anywhere banking) at any time. Providing Internet banking is increasingly becoming a "need to have" than a "nice to have" service.